Analysis of functional Shrikhand incorporated with orange fruit peel extracts - Agalya, A; Pugazhenthi, T R; Narayanan, Rita; Bharathidhasan, A; Sowmya, V (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Shrikhand is a traditional fermented dairy product with added nutritional profile. The present study encompasses on analyzing the functional properties viz. phenolic content, antioxidant activity, microbial quality and calorific value of functional shrikhand incorporated with orange fruit peel extract. The statistical analysis inferred that extracts of orange contained phenolic content in the range of 7.78±0.36 to 16.25±0.94 mg/g during storage. The ethanol extracts incorporated functional shrikhand presented higher antioxidant activity (17.74 to 34.25%) than that of aqueous extracts (14.35 to 33.64%) of orange peel. On further comparison, the dried fruit peel extracts offered more TPC and antioxidant activity (16.25±0.94 to 10.85±0.21 and 34.25±0.05 to 22.80±0.31%) than fresh fruit peel extracts (15.85±0.39 to 7.78±0.36 and 28.58±0.15 to 14.35±1.09) respectively. The orange fruit peel incorporated functional shrikhand can be stored up to 15 days at 5°C without affecting the overall sensory acceptability with enhanced antioxidant activity and total phenolic content and it could be used as dairy supplement in human diet.